'A Missing Piece of European Emergency Law: Legal Certainty and Individuals' Expectations in the EU Response to the Crisis'. (18th August 2016) - Martín Rodríguez, Pablo
Abstract : The principle of legal certainty and legitimate expectations as a legal tool for individuals in EU law – the mixed nature of EU emergency law: the 'conferral principle' limitation and the ways to expand executive powers in the EU response to the crisis ( Pringle, ESMA, BPP, OMT ) – the existence of legal certainty failures in that response: unpredictable and disjointed legislation and adjudication – arguments blurring legal certainty as the standard of review for EU emergency law: conditionality, international law and indirect legislation – the self-restraint attitude of the European Court of Justice and the risks of leaving litigation under the sole remit of national courts: normalising emergency powers and EU law autonomy at stake